Universal credit: Incomes, incentives and the remaining roll-out - Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2024)
The introduction of universal credit (UC) has been the most significant reform to the workingage benefits system since the reforms following the post-war Beveridge Report. When fully rolled out, around 8 million families - 29% of all working-age families - will be entitled to the benefit. UC is an integrated means-tested benefit that is replacing six 'legacy' benefits, combining out-of-work support with support for housing costs, incapacity and children. This report assesses the impact of the UC reform on households' incomes and their financial incentives to work, as well as the practical experience of applying for and getting means-tested benefits. We then briefly review the issues around the rest of UC's roll-out.
Keywords: 330; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Distributional effects; Labour supply and workforce; Universal credit; Working age benefits